The neutrophil-to-lymphocyte ratio in children with sudden sensorineural hearing loss: a retrospective study. (2nd January 2017) - Lee, Joong Seob; Hong, Sung Kwang; Kim, Dong Hyun; Lee, Ju Han; Lee, Hyo-Jeong; Park, Bumjung; Choi, Hyo Geun; Kong, Il Gyu; Song, Hong Ji; Kim, Hyung-Jong
Abstract: Conclusion: The elevated neutrophil-to-lymphocyte ratio (NLR) value in children with sudden sensorineural hearing loss (SSNHL) would suggest the inflammatory etiology of pediatric SSNHL. The results of this study may suggest NLR value can be used as a useful indicator, which is associated with the disease severity in pediatric SSNHL. Objectives: This study aimed to elucidate any clues of inflammatory etiology, which might be related with the development of pediatric SSNHL, using calculated NLR. Methods: Forty-six patients aged younger than 19 years, who were admitted to the hospital with the diagnosis of SSNHL, were included in the study. Forty-six healthy children were matched as control group according to their propensity score. The complete blood cell count, calculated NLR, platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) were compared. The relationship between NLR and the initial hearing level was also investigated. Results: The mean NLR value was 2.86 ± 2.58 in the SSNHL group, whereas the mean NLR value was 1.63 ± 0.87 in the control group. The mean NLR value of the SSNHL children was significantly higher than that of the control group ( p  = .023). There was a positive correlation between the NLR value and initial hearing level ( r  = .312, p  = .037).